Dyslipidemia in Chronic Kidney Disease Patients at Dr. Soetomo Hospital Surabaya - Siti Rahmawati; Jusak Nugraha; Edhi Rianto (Media Penelitian dan Pengembangan Kesehatan, 2021)
Epidemiological studies report that patients with chronic kidney disease (CKD) have a higher risk of mortality from cardiovascular disease than the general population. Previous studies have shown that dyslipidemia is thought to play a role in the development of atherosclerosis in patients with CKD. Dyslipidemia is known to be common in CKD patient population, but shows a diverse patterns in various CKD patient populations. This study aimed to analyze the lipid profile and lipid ratio in CKD patients at Dr. Soetomo Hospital Surabaya for the period 2016-2017. This cross-sectional study was conducted through retrospective observation of the medical records of CKD patient at the Kidney-Hypertension Polyclinic of Dr. Soetomo Hospital Surabaya in the 2016-2017 period. A total of 68 research subjects were analyed in this study. Most of the study subjects were male (68%) and the median age was 54 years. Almost 70% of the study subjects had CKD stage 5. Increased levels of total cholesterol and triglyceride were found in 37% of the study subjects. Meanwhile, a decreae in HDL-cholesterol levels and an increase in LDL-cholesterol and non-HDL-cholesterol levels were found in 60% of the study subjects. The mean value of total cholesterol, LDL-cholesterol, and non-HDL-cholesterol levels in the female group was siginificantly higher based on statistical calculations (p0.05). Most of the study subjects were predicted to be at risks for developing cardiovascular disease based on the calculation of several lipid ratios. The incidence of dyslipidemia in population is known to be higher than in the general population. Decreased HDL-cholesterol, increased LDL-cholesterol, and non-HDL-cholesterol are the most common forms of dyslipidemia in population studies. Abstrak Studi epidemiologi melaporkan bahwa pasien penyakit ginjal kronis memiliki risiko mortalitas akibat penyakit kardiovaskular yang lebih tinggi dibandingkan populasi umum. Studi sebelumnya menunjukkan bahwa dislipidemia diduga turut berperan terhadap terjadinya atherosklerosis pada pasien penyakit ginjal kronis. Dislipidemia diketahui umum ditemukan pada populasi pasien penyakit ginjal kronis namun menunjukkan pola yang bervariasi pada berbagai populasi pasien penyakit ginjal kronis. Studi ini bertujuan untuk menganalisis profil lipid dan rasio lipid pada pasien penyakit ginjal kronis di RSUD Dr. Soetomo Surabaya periode 2016-2017. Studi cross-sectional ini dilakukan melalui pengamatan retrospektif terhadap catatan rekam medis pasien penyakit ginjal kronis di Poliklinik Ginjal-Hipertensi RSUD Dr. Soetomo Surabaya pada periode 2016-2017. Sebanyak 68 subjek penelitian dianalisis dalam penelitian ini. Sebagian besar subjek penelitian berjenis kelamin laki-laki (68%) dan nilai median usia pada subjek penelitian mencapai 54 tahun. Sebagian besar subjek penelitian memiliki penyakit ginjal kronis stadium 5 (70%). Peningkatan kadar kolesterol total dan trigliserida ditemukan pada sekitar 37% subjek penelitian. Sedangkan penurunan kadar HDL-kolesterol dan peningkatan kadar LDL-kolesterol serta non HDL-kolesterol ditemukan pada sekitar 60% subjek penelitian. Nilai rerata kadar kolesterol total, LDL-kolesterol, dan non HDL-kolesterol pada kelompok berjenis kelamin perempuan secara signifikan lebih tinggi berdasarkan perhitungan statistika (p0.05). Sebagian besar subjek penelitian diprediksi memiliki risiko untuk mengalami penyakit kardiovaskular berdasarkan perhitungan beberapa rasio lipid. Insiden dislipidemia pada studi populasi diketahui lebih tinggi dibandingkan populasi umum. Penurunan HDL-kolesterol, peningkatan LDL-kolesterol, dan non HDL-kolesterol merupakan bentuk dislipidemia yang paling umum ditemukan pada studi populasi.